Internal Reliability and Validity of Pediatric Symptom Checklist-17 Indonesian Version for Behavioral Problem Identification in Adolescent Population - Irwanto, - (Department of Cardiology, School of Medicine, The University of Tokyo, 2020)
We developed a thematic, Indonesian-translated version, of Pediatric Symptom Checklist 17 (PSC-17) to assess the prevalence of the behavioral problem in the adolescent population. This study is a cross-sectional study aiming to assess the validity and reliability of PSC-17 in the Indonesian language. A questionnaire of seventeen questions was prepared to assess behavioral problems in the form of attention, internalizing, and externalizing symptoms. The study population is adolescents aged 15-17 years old in Gorontalo City, Province of Gorontalo, Indonesia. Subjects were asked to self-answer the questionnaire. The scale of the problem in internalizing, attention, and externalizing subscales were calculated from the obtained results. Validity was measured by using Pearson correlation strength test and reliability was measured by using Cronbach’s Alpha reliability test. As many as 384 participants were enrolled, in which 380 complete answers towards the PSC-17 Indonesian Version were obtained. Pearson correlation strength test showed that PSC-17 is valid under the Pearson r product moment of df = 378 under two-tailed alpha α = 0.05 (p<0.001). Cronbach’s Alpha reliability test showed high reliability of the PSC-17 (α=0.821). Based on our findings, Indonesian version PSC-17 is a valid and highly reliable set of questions to assess pediatric behavioral problems, especially in the adolescent population.